Diabetes and Pancreatic Cancer - El-Jurdi, Najla Hatem; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
There is great emphasis on early identification of high risk patients for developing pancreatic cancer in an attempt to reduce the burden of the fourth leading cause of cancer death in the United States. Abstracts presented at the 2013 American Society of Clinical Oncology (ASCO) Annual Meeting highlighted and supported the relationship between pancreatic cancer and diabetes mellitus and Abstract #4039 showed that hemoglobin-A1c at the time of diagnosis correlates with disease stage and predicts survival among all stages of pancreatic cancer patients. Abstracts #4044 and #e15110 also presented in 2013 ASCO Annual Meeting showed that metformin treatment serves as a positive prognosticator, especially in patients with diabetes mellitus diagnosed within 2 years of pancreatic cancer and in stage 3 pancreatic cancer patients with diabetes mellitus. Image: Metformin activates AMPKThr172 through the LKB1 signalling pathway.